Hypervitaminosis D has no positive effects on goat tuberculosis and may cause chronic renal lesions. (21st December 2019) - Risalde, Maria Angeles; Roy, Álvaro; Bezos, Javier; Pineda, Carmen; Casal, Carmen; Díez‐Guerrier, Alberto; Lopez‐Villalba, Ignacio; Fernández‐Manzano, Álvaro; Moreno, Inmaculada; De Juan, Lucía; Domínguez, Lucas; Gortazar, Christian
Abstract : Background: There is evidence for a link between vitamin D deficiency and active tuberculosis (TB). In human beings, several trials have evaluated the role of vitamin D supplementation in TB treatment with conflicting results. However, the role of vitamin D supplementation in animal TB control has received less attention. The authors evaluated the beneﬁt of vitamin D supplementation for preventing mycobacterial infection or reducing TB lesions (TBL) in a controlled trial with goats naturally exposed to Mycobacterium caprae . Methods: Two groups of goats, a vitamin D‐supplemented group and a non‐supplemented control group, were housed for 10 months in direct contact with M caprae ‐infected adult goats. Upon contact with the infected adult goats, all animals were TB‐tested every two months. Results: No experimental evidence of a protective effect of vitamin D supplementation based on M caprae culture prevalence, TBL prevalence, median TBL score or the proportion of single versus multiple organs presenting TBL was observed. Conclusion: The results indicate that, in the conditions used in this study, vitamin D supplementation in goats does not reduce TB infection risk nor the diffusion and severity of TBL. In addition, vitamin D‐supplemented goats presented hyperphosphataemia and renal injury with calcifications suggestive of vitamin D intoxication.